Dissemination of innovation in Bangladeshi aquaculture: The importance of targeted approaches based on farm characteristics - Ramachandran, Rohit; Dam Lam, Rodolfo; Saito, Osamu; Rossignoli, Cristiano; Barman, Benoy (Institute for Global Environmental Strategies, 2023)
Climate change, flooding, disease and lack of proper governance are creating unforeseen challenges for aquaculture development in Bangladesh. Identifying the various characteristics of the aquaculture production systems and designing approaches based on those characteristics can be valuable in identifying and disseminating innovative solutions to the newly arising problems in aquaculture in Bangladesh.